Comparison of muscle activity during 200 m indoor curve and straight sprinting in elite female sprinters - Pietraszewski, P.; Golas, A.; Krzysztofik, M. (Journal of Human Kinetics, 2021)
The purpose of this study was to assess whether peak surface electromyography (sEMG) amplitude of selected lower limb muscles differed during a) curve and straight sprinting, b) sprinting in inside and outside lanes between lower limbs. Eleven well-trained female sprinters (personal best: 24.1 ± 1.1 s) were included in a randomized within-subject design study, in which participants underwent two experimental conditions: all-out 200 m indoor sprints in the innermost and outermost lane. Peak sEMG amplitude was recorded bilaterally from gastrocnemius medialis, biceps femoris, gluteus maximus, tibialis anterior, and vastus lateralis muscles. Left gastrocnemius medialis peak sEMG amplitude was significantly higher than for the right leg muscle during curve (p = 0.011) and straight sprinting (p < 0.001) when sprinting in the inside lane, and also significantly higher when sprinting in the inside vs. outside lane for both curve and straight sprinting (p = 0.037 and p = 0.027, respectively). Moreover, left biceps femoris peak sEMG amplitude was significantly higher during straight sprinting in the inside vs. outside lane (p = 0.006). Furthermore, right and left vastus lateralis peak sEMG amplitude was significantly higher during curve sprinting in the inside lane (p = 0.001 and p = 0.004, respectively) and for the left leg muscle peak sEMG amplitude was significantly higher during curve compared to straight sprinting in the outside lane (p = 0.024). Results indicate that curve sprinting creates greater demands mainly for the gastrocnemius medialis of the inner than the outer leg, but the degree of these requirements seems to depend on the radius of the curve, thus significant changes were noted during sprinting in the inside lane, but not in the outside lane.